Feasibility of a low-cost magnet tracking device in confirming nasogastric tube placement at point of care, a clinical trial - Li, Hao (2024)
An affordable and reliable way of confirming the placement of nasogastric tube (NGT) at point-of-care is an unmet need. Using a novel algorithm and few sensors, we developed a low-cost magnet tracking device and showed its potential to localize the NGT preclinically. Here, we embark on a first-in-human trial. Six male and 4 female patients with NGT from the general ward of an urban hospital were recruited. We used the device to localize the NGT and compared that against chest X-ray (CXR). In 5 patients, with the sensors placed on the sternal angle, the trajectory of the NGT was reproduced by the tracking device. The tracked location of the NGT deviated from CXR by 0.55 to 1.63 cm, and a downward tracking range of 17 to 22 cm from the sternal angle was achieved. Placing the sensors on the xiphisternum, however, resulted in overt discordance between the device's localization and that on CXR. Short distance between the sternal angle and the xiphisternum, and lower body weight were observed in patients in whom tracking was feasible. Tracking was quick and well tolerated. No adverse event occurred. This device feasibly localized the NGT in 50% of patients when appropriately placed. Further refinement is anticipated.ClinicalTrials.gov identifier: NCT05204901.